FRESHWATER FISH PRODUCT PROCESSING IN PULOTONDO VILLAGE, TULUNGAGUNG REGENCY, EAST JAVA - Buwono, Haris Puspito; Ramadhana, Rucita; Ariani, Ariani; Chalim, Abdul; Rachmawati, Diana (LPPM Univ. Ibn Khaldun Bogor, 2024)
Freshwater fish cultivation in Pulotondo Village, Ngunut District, Tulungagung Regency, East Java, has significant potential to increase income and improve the well-being of the community while fostering sustainable economic growth. Ponds managed collectively by the Village-Owned Enterprises (BUMDES) serve as a facility for freshwater fish cultivation, with an annual production of 220 tons. One of the obstacles to the development of this business is the enhancement of the value and shelf life of processed fish products. Therefore, the Community Service activity in Pulotondo Village focuses on training in the processing of freshwater fish products. Through this initiative, BUMDES and the community can enhance understanding and skills, enabling processed products to be stored longer and have a more competitive market value. To assess the training's impact, participants provided feedback through a questionnaire. The results indicate that the training activities were well-understood by the participants, showing an indication of increased entrepreneurial spirit through local potential.